El marco de la historia : el papel de la profecía en la Historia regum Britanniae de Geoffrey de Monmouth (2015)
ABSTRACT: This article will use close textual analysis in order to examine the role played by prophecy and the supernatural in Geoffrey of Monmouth’s Historia Regum Britanniae. This immensely popular and influential work includes three instances of prophetic vision: the first comes early in the narrative in a pagan setting when Bruto, the mythical founder of Britain, receives a message from the goddess Diana, in a dream; the last vision is a divine revelation from an angel to the last Cristian king of Britain, Cadwallader; during the peak of the narrative, king Arthur also experiences a dream-vision. This article shows that these three instances of prophecy frame the narrative around the «passage of dominion», acting as its structural points. In Geoffrey’s text, dream-visions and prophecies frame the narrative, and therefore they also frame History.